Turning date palm fronds into biocompatible mesoporous fluorescent carbon dots. Issue 1 (December 2018) - Kavitha, T.; Kumar, S.
Abstract Here, we demonstrate the synthesis of mesoporous carbon dots (Cdot) from date palm fronds and their excellent excitation wavelength-independent photoluminescence (PL), with high photo- and storage-stability, superior biocompatibility and thermal and electrical conductivity for the first-time by a simple, green, one-step carbonization method. Interestingly, the as-obtained Cdot manifest the spherical shape of about 50 nm average diameter having surface mesopores of size less than 10 nm withsp 2 hybridized carbon. The as-synthesised mesoporous Cdot, first of its kind, evince yellow-green PL (preferred over blue PL for biological applications) around 450 nm under excitation wavelength range of 320–420 nm with absolute quantum yield of 33.7% exhibiting high photo- and storage-stability. The thermal and electrical conductivity of Cdot/water nanofluids without any surfactants is illustrated. Application of Cdot as interfacial material in organic photovoltaic cell is manifested. The Cdot exhib visible sunlight driven photocatalytic and antibacterial activity. Mesoporous Cdot further reveal excellent biocompatibility with fibroblast cell (greater than 95% viability). The novelty of this study in the formation of multifunctional mesoporous Cdot from date palm fronds could inspire both research and industrial interests in the synthesis of biomass-derived Cdot and their application in a wide array of fields.